Mechanical Damage Test and Model Study of Layered Composite Rock Based on Acoustic Emission and DIC Characteristics - Xianyin Qi; Zhen Yang; Shengwei Wang; Peng Fu (Shock and Vibration)
To study the mechanical damage characteristics of layered composite rocks, sandstones, and mudstones of deep tight reservoirs were used as the research objects, and layered composite class rocks were prepared by similar material model tests. Uniaxial compression tests were conducted and supplemented with AE (Acoustic Emission) system and DIC (Digital Image Correlation) system to obtain the physical and mechanical parameters such as strength and elastic modulus of the layered composite rocks. The corresponding law of AE ringing count and rock damage evolution was studied and the damage process of layered composite rock under uniaxial loading was divided into three stages: initial damage, stable damage development, and damage acceleration. Analysis of strain cloud diagrams of the DIC system revealed that the deformation characteristics of the layered composite rock under uniaxial were mainly tensile-shear-slip damage. Based on the internal damage evolution characteristics of AE and the surface damage evolution characteristics of DIC, a damage constitutive model of layered composite rocks based on the dual damage factor characterization was established, which reasonably revealed the damage evolution mechanism of internal structure development and external crack germination, extension and penetration of layered composite rocks under uniaxial compression.